Academic Motivation and Achievement in Undergraduate Students of the Medical Program, Faculty of Medicine, Tanjungpura University, during the COVID-19 Pandemic - Yandion, Imanda; Fitrianingrum, Iit; Pratiwi, Sari Eka (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: Most students had very high academic motivation and achievement in the very satisfactory category. No correlation between academic motivation and achievement in undergraduate students.   Abstract Introduction: Academic motivation is said to be correlated to academic achievement. The coronavirus disease (COVID-19) pandemic has led to a distance learning policy allowing students to continue their education. Distance learning has several impacts that can result in students' academic motivation. Therefore, it affects academic achievement. This study examined the relationship between academic motivation and achievement in undergraduate students of the Medical Study Program, Faculty of Medicine, Tanjungpura University, during the COVID-19 Pandemic. Methods: This was an observational analytic study with a cross-sectional approach. A total of 169 students (n=169) were selected through a stratified random sampling technique. Data was processed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 24.0. The variables were measured using the Academic Motivation Scale (AMS)—Short Indonesian Language Version questionnaire and the student's Grade Point Average (GPA). The Spearman Rank correlation test showed a significance value of 0.096 (Sig>0.05; r=0.128). Results: The results showed that most of the samples had very high academic motivation (71.6%) and academic achievement in the very satisfactory category (51.5%). Spearman Rank correlation test showed a significance value of 0.096 (Sig>0.05; r=0.128). Conclusion: There was no correlation between academic motivation and achievement in undergraduate students of the Medical Program, Faculty of Medicine, Tanjungpura University, during the COVID-19 pandemic.